2015
DOI: 10.1111/bjd.13544
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy, photodynamic therapy and photophoresis in the treatment of connective-tissue diseases: a review

Abstract: Connective-tissue disorders, which include lupus erythematosus, morphoea/scleroderma and dermatomyositis, are characterized by cutaneous manifestations that are sometimes resistant to conventional therapy. Light treatments, which include phototherapy, photodynamic therapy (PDT) and photopheresis, are routinely utilized in the treatment of dermatological conditions and may provide unique mechanisms of action in the treatment of these connective-tissue disorders. The objective of this study is to conduct a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…Connective‐tissue disorders, including lupus erythematosus (LE) and morphea/scleroderma, are characterized by cutaneous manifestations which prove sometimes resistant to conventional therapy. Given the association of some of these conditions with photosensitivity, the use of lightbased therapeutic modalities for their treatment may be counterintuitive 23 . However, the potential of localized tissue destruction in exposed areas by PDT may be useful in certain instances.…”
Section: Potential Indications For Pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…Connective‐tissue disorders, including lupus erythematosus (LE) and morphea/scleroderma, are characterized by cutaneous manifestations which prove sometimes resistant to conventional therapy. Given the association of some of these conditions with photosensitivity, the use of lightbased therapeutic modalities for their treatment may be counterintuitive 23 . However, the potential of localized tissue destruction in exposed areas by PDT may be useful in certain instances.…”
Section: Potential Indications For Pdtmentioning
confidence: 99%
“…Regarding cutaneous LE, particularly its chronic forms, studies have shown a clinical response to PDT in 60% of the patients, with durable responses (no recurrence at 6‐months follow‐up) 23 . Although formal recommendations on the use of PDT in cutaneous LE are limited, this may become a therapeutic alternative for patients with recalcitrant forms in the future.…”
Section: Potential Indications For Pdtmentioning
confidence: 99%
“…Due to concerns of phototoxicity and potential exacerbation of photosensitive disorders, many dermatologists may hesitate to prescribe NBUVB phototherapy to patients with vitiligo with concurrent positive serum ANA. NBUVB is often avoided in patients with vitiligo with photosensitive disorders, as subsequent inflammation induced by irradiation can stimulate the immune system, antibody formation, and exacerbation of photosensitive diseases . It is thought that NBUVB radiation induces a predominantly type 2 immune response, which may result in elevation of ANA …”
Section: Discussionmentioning
confidence: 99%
“…Prior to administration of NBUVB phototherapy, a complete physical examination is recommended to ensure there are no obvious signs of other underlying diseases, especially photosensitive disorders . In the presence of photosensitive disorders such as systemic lupus erythematosus (SLE), UVB is avoided due to phototoxicity (defined here as a skin burning reaction to phototherapy; eg, erythema, peeling, blistering) as irradiation results in an inflammatory skin reaction with keratinocyte necrosis, which can induce stimulation of the immune system, formation of antibodies, and ultimately exacerbate SLE disease …”
Section: Introductionmentioning
confidence: 99%
“…[85][86][87][88] Photochemical/photodynamic treatments using exogenous photoactive agents add a further degree of molecular specificity over and above the light targeting. [89][90][91] These act through a variety of photobiological mechanisms: necrotic, apoptotic or autophagic tumor cell kill; damage to the microvasculature as in treatment of age-related macular degeneration, 92 AMD; 93 and/or triggering of systemic immune responses. 94,95 These cytotoxic effects are mediated by the photogeneration of excited radical states, such as singlet oxygen, which has also been a primary focus in the development of radiation-enabled phototherapeutics, as discussed below.…”
Section: Current Biomedical Optics Technologiesmentioning
confidence: 99%